2014
DOI: 10.1007/s11427-014-4701-7
|View full text |Cite
|
Sign up to set email alerts
|

Intermedin/adrenomedullin2: an autocrine/paracrine factor in vascular homeostasis and disease

Abstract: Intermedin (IMD) or adrenomedullin 2 is a novel peptide related to the calcitonin gene-related peptide (CGRP) family. Via calcitonin receptor-like receptor/receptor activity modifying proteins, the common receptor complexes of CGRP, IMD exerts a wide range of biological effects, especially regulation of cardiovascular homeostasis. Proteolytic processing of a larger IMD precursor yields a series of biologically active C-terminal fragments, IMD1-53, IMD1-47 and IMD8-47. IMD and its receptors are present in the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 38 publications
0
29
0
Order By: Relevance
“…Human IMD gene is located on the distal arm of chromosome 22, and its prepropeptide is composed of 148 amino acids, named prepro-IMD. Prepro-IMD can yield IMD 1–47 (prepro-IMD 101—147 ), IMD 8–47 (prepro-IMD 108–147 ), and IMD 1–53 (prepro-IMD 93–145 ) by proteolytic cleavage and amidation 26) . IMD has the similar effects with adrenomedullin.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Human IMD gene is located on the distal arm of chromosome 22, and its prepropeptide is composed of 148 amino acids, named prepro-IMD. Prepro-IMD can yield IMD 1–47 (prepro-IMD 101—147 ), IMD 8–47 (prepro-IMD 108–147 ), and IMD 1–53 (prepro-IMD 93–145 ) by proteolytic cleavage and amidation 26) . IMD has the similar effects with adrenomedullin.…”
Section: Introductionmentioning
confidence: 99%
“…Adrenomedullin receptor activity modifying protein (RAMP)2 system can maintain vascular integrity and homeostasis 27) . IMD can also maintain cardiovascular homeostasis via its calcitonin receptor-like receptor (CRLR)/RAMP complexes 26) . Our previous study showed that in CFs, endogenous IMD was significantly decreased in response to Ang II treatment, and administration of IMD 1–53 suppressed Ang II-induced activation of CFs and hypertrophy of cardiomyocytes 28, 29) .…”
Section: Introductionmentioning
confidence: 99%
“…The symptoms of PH were alleviated with ADM2/IMD treatment in rats, the right ventricular hypertrophy was prevented and the hypoxic pulmonary vascular remodeling was inhibited 111 . According to these studies that were performed in pulmonary hypertensive rats, ADM2/IMD is thought to be effective in PH 118 . In chronic hypoxiainduced PH ADM2/IMD provided potent vasodilation in pulmonary arteries of rats and intraarterial administration was reduced the perfusion pressure of hypoxic lungs.…”
Section: U N C O R R E C T E D P R O O Fmentioning
confidence: 99%
“…Intermedin (IMD), also named as adrenomedullin-2, a member of the calcitonin/calcitonin gene-related peptide (CGRP) family, exerts a wide range of biological effects, especially in maintaining cardiovascular homeostasis [8]. The possible mechanism may be related to the upregulation in cAMP level in the circulatory system, and regulation of the proliferation of the smooth muscle and up-regulating NO system [9].…”
Section: Introductionmentioning
confidence: 99%